Investigating the role of the cellular RNA decay pathway during flavivirus replication - Denis, Denis, author; Geiss, Brian, advisor; Willusz, Jeffrey, committee member; Ebel, Gregory, committee member; Snow, Christopher, committee member (Colorado State University. Libraries, 2022)
The Cellular RNA decay pathway is an important regulatory system that affects both the quality and quantity of mRNA within the cells. Previous studies have shown that RNA viruses develop evasion mechanism to the cellular RNA decay pathway due to its antiviral nature. In eukaryotic cells, 5'-3' exonucleolytic decay mediated by XRN1 is known to be the major RNA decay pathway that interacts with RNA viruses. To provide RNA substrates for XRN1 degradation, cellular mRNA and viral RNA need to be processed by decapping enzymes such as DXO and DCP2 or RNA triphosphatases such as DUSP11 and NUDT2. Currently, there are few studies that have examined the roles of these proteins during RNA virus replication. In this study, we performed a loss-of-function experiment utilizing siRNA-mediated knockdown to reduce various RNA decay proteins and examine their effects on flavivirus replication. Collectively, our data suggested that knocking down DUSP11 and NUDT2 did not significantly affect the replication of infectious flaviviruses, whereas depletion of DCP2, showed significantly diminished West Nile virus and Zika virus replication but not on yellow fever virus. The results of this project indicate that DCP2 acts as a proviral factor for several but not all flaviviruses during infection and provide new insight into how flaviviruses may generate RNAs for XRN1-mediated degradation and subsequent XRN1 inhibition.
Keywords: DUSP11; flavivirus; RNA decay pathway; DXO; DCP2; NUDT2